2013
DOI: 10.1007/s00404-013-3128-x
|View full text |Cite
|
Sign up to set email alerts
|

Serum soluble mesothelin-related peptide (SMRP): a potential diagnostic and monitoring marker for epithelial ovarian cancer

Abstract: Serum SMRP is a promising marker for the diagnosis and monitoring of EOC, especially in combination with CA125.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 27 publications
0
16
0
Order By: Relevance
“…Many studies showed that serum mesothelin levels are related to the FIGO surgical pathological staging and pathological grade in EOC patients. Patients with advanced stage and low differentiation tumors showed higher levels of SMRP most recent study reported the expression of mesothelin in ovarian tissue correlated to chemotherapy resistance and poor prognosis suggesting a role for mesothelin in diagnosis and disease staging [32].…”
Section: Mesothelinmentioning
confidence: 99%
“…Many studies showed that serum mesothelin levels are related to the FIGO surgical pathological staging and pathological grade in EOC patients. Patients with advanced stage and low differentiation tumors showed higher levels of SMRP most recent study reported the expression of mesothelin in ovarian tissue correlated to chemotherapy resistance and poor prognosis suggesting a role for mesothelin in diagnosis and disease staging [32].…”
Section: Mesothelinmentioning
confidence: 99%
“…[30][31][32][33][34] The presence of SMRP can also alter the binding capacity of mesothelin-targeting therapeutic agents. 22,23 On the basis of these data, we used the serum of 21 patients with metastatic colon and pancreatic cancers in competition assays with selected Fabs.…”
Section: Competition Tests With Smrp In Patients' Serum and Cell Supementioning
confidence: 99%
“…Mesothelin, a membrane-bound peptide, is consistently present in normal mesothelial cells and overexpressed in many malignancies including mesothelioma, ovarian, colon, gastric, lung, triple-negative breast cancer, and pancreatico-biliary adenocarcinomas [5][6][7][8][9][10][11]. The mesothelin gene encodes a 69-71-kDa polypeptide anchored to the cell membrane by a glycosyl-phosphatidyl-inositol (GPI) linkage that can be processed to yield mesothelin, which remains attached to cell membrane, and another protein called MPF secreted into the blood [12][13][14].…”
Section: Smrpmentioning
confidence: 99%